Exploring Teachers' Perspectives on Promoting the Application of Mathematics in Unfamiliar Situations: A Case Study - Rani, Neeta; Lal, Dori (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2025)
Various commissions and policies stressed on the importance of connecting mathematics to unfamiliar situations while teaching. Position paper of mathematics of National Curriculum Framework (2005) suggested two types of goals of teaching mathematics: broader goal and narrow goal. Broader goal of teaching mathematics is mathematisation and narrow goal is numeracy and computation. But the literature suggests that in present day classroom mathematics teaching practices, component of promoting connection with unfamiliar situations is insufficient and infrequent. Rather few studies particularly suggest whether, how and why teachers should connect mathematics to unfamiliar situations. In this paper, the researchers tried to answer the question: what is the perspective of teachers regarding ability of students to apply mathematics in unfamiliar situations? For answering this question, the researchers conducted a survey with 30 secondary mathematics teachers of 10 different Delhi government schools. The survey contains items that indicate about the factors that promote and/or constrain the ability of students to connect mathematics to unfamiliar situations. Survey is followed up by interview of 10 teachers out of 30 to triangulate the results. The results obtained give an insight about the perspective of teachers as well as suggest other important issues for further research. Moreover, the results may be helpful while devising different mathematics teaching strategies according to varying needs of learners